Analisis Dukungan Keluarga Pada Respon Cemas Anak yang Terpasang Infus - Fatriansari, Asih; Lestari, Indah Dwi; Astuti, Lenny (Universitas Malahayati, 2023)
ABSTRACT Children are very susceptible to disease so that it can cause children to be hospitalized. One of the nursing actions carried out in the hospital is the installation of infusions, so many infusions are performed on most of the patients being treated. Anxiety that arises in children because of a sense of pressure and fear, support from the family is needed, because the family is an important element in care. Determine family support on the anxious response of children who are infusions. Research uses descriptive analytical method. Sampling in this study used the Accidental Sampling technique. Data was collected by using the questionnaire method. The population in this study were all inpatients in the Medina Room of Siti Khadijah Hospital Palembang in 2022 with a total sample of 32 respondents. Result of this study showed that of the 32 respondents who had good family support, there were 21 respondents (65.6%), more when compared to respondents who had poor family support, namely 11 respondents (34.4%). That good family support is more than bad family support. It is hoped that this research hospital can provide health education to parents of children who are hospitalized. Keywords: Family Support, Anxiety Response, Intravenous ABSTRAK Anak sangat rentan terkena penyakit sehingga dapat menyebabkan anak harus dirawat di Rumah Sakit. Salah satu tindakan keperawatan yang dilakukan di Rumah Sakit adalah pemasangan infus, tindakan pemasangan infus begitu banyak dilakukan pada sebagian besar pasien yang dirawat. Kecemasan yang timbul pada anak karena adanya rasa tertekan dan ketakutan maka, dukungan dari keluarga sangat di perlukan, karena keluarga adalah unsur penting dalam perawatan. Untuk mengetahui dukungan keluarga pada respon cemas anak yang terpasang infus. Menggunakan metode Desktipstif Analitik. Pengambilan sampel penelitian ini menggunakan teknik Accidental Sampling. Pengumpulan data dilakukan dengan metode kuesioner. Populasi dalam penelitian ini adalah seluruh pasien rawat inap di Ruang Madinah RSI Siti Khadijah Palembang Tahun 2022 dengan jumlah sampel sebanyak 32 responden. Penelitian didapatkan bahwa dari 32 responden yang memiliki dukungan keluarga baik sebanyak 21 responden (65,6%), lebih banyak jika dibandingkan dengan responden yang memiliki dukungan keluarga kurang baik yaitu 11 responden (34,4%). Dukungan keluarga baik lebih banyak dari pada dukungan keluarga kurang baik. Kata Kunci: Dukungan Keluarga, Respon Cemas, Terpasang Infus